# 6-1*0+2/2=

*print*Print*list*Cite

### 12 Answers

Using BEDMAS (or PEMDAS if you learned that expression instead) we get

`6-1 times 0+2/2` multiplication and division first

`=6-0+1` left to right with addition and subtraction

`=6+1`

`=7`

**The expression simplifies to 7.**

Here is a video explaining the order of operations.

6-(1x0)+(2/2)

6-0+1

6+1

7

6-1*0+2/2

Use PEMDAS for this equation

6-(0) =1

**7**

Equation:

6-1*0+2/2= ?

Follow PEMDAS

**P**arenthesis

**E**xponent

**M**ultiplication

**D**ivision

**A**ddition

**S**ubstraction

6-1*0+2/2=

**7**

6 - 1 X 0 + 2/2 =

Remember to follow the order of PEMDAS

**P**arenthesis

**E**xponents

**M**ultipication

**D**ivision

**A**ddition

**S**ubtraction

First, multiply -1 and 0

By doing that your equation should look like

**6 + 2/2 **Now divide 2 by 2

By dividing 2 by 2 your equation should look like

**6 + 1 **now add

By adding it should be

**= 7 **which is your answer

6-1*0+2/2=

follow pemdas

6-0+2/2

6+2/2

6+1

7

6-1*0+2/2=

So using PEMDAS

6-1*0+2/2=

6-0+2/2=

6-0+1=

6+1= 7

Using Please Excuse My Dear Aunt Sally (Parenthesis, Exponent, Multiplication, Division, Addition, Subtraction

Do all the multiplication and division parts first, reading from left to right :

6-1*0+2/2=

6 - 0 + 1

Then do all the addition and subtraction, reading from left to right :

7

6-1*0+2/2

6-0+1=7

6-1*0+2/2

6-0+1

6+1

7

6-1*0+2/2

6+1=7

Hi,

6-1*0+2/2=6-0+1=7